FAKTOR RISIKO YANG MEMPENGARUHI KEJADIAN HIPERENSI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU, KOTA SEMARANG TAHUN 2017 - Imaroh, Istiana Islahul; Nugraheni, Sri Achadi; Dharminto, Dharminto (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
ABSTRACTHypertension is the most common medical problem encountered during pregnancy, complicating up tp 2-3% of pregnancies. Hypertensive disorder during pregnancy is still become one of the major causes for maternal mortality in Indonesia. The aim of this research was to analyzed risk factors for hypertensive disorder of pregnancy in Kedungmundu Health Center Area, Semarang City. This research was an analytical descriptive with case control design. The sample of this research were 44 pregnant, which were consisted of 22 cases and 22 controls. They were analyzed using chi square test with continuity correction (Yates). Results of this research showed that were correlatoions and risk factors for maternal age (CI =1,345-18,205; OR=4,911), motherâ€™s education (CI =1,203-23,158; OR=5,278), employment (CI=1,732-33,347; OR=7,600), income (CI=1,560-20,929); OR=5,714), gravida (CI=2,306-35,650); OR=4.667), family hypertension history (CI=1,586-22,328; OR= 5,950), body mass index (CI=1,299-16,761; OR=4,667), consumption of sodium (CI=1,905-27,861; OR=7,286), but abortion history (CI=0,518-7,291; OR=1,943) was not correlateÂ  and was not risk factor. Thisresearch recommends that health officers should gave routine counseling about risk factors of pregnancy hypertension for group pregnant who had risk of hypertension, and pregnant is expected to routinely conduct examination in health center, and for further research can dig deeper cause of risk factor and use another variable.